2015
DOI: 10.1103/physreve.91.022301
|View full text |Cite
|
Sign up to set email alerts
|

Inherent structures, fragility, and jamming: Insights from quasi-one-dimensional hard disks

Abstract: We study a quasi-one-dimensional system of hard disks confined between hard lines to explore the relationship between the inherent structure landscape, the thermodynamics, and the dynamics of the fluid. The transfer matrix method is used to obtain an exact description of the landscape, equation of state, and provide a mapping of configurations of the equilibrium fluid to their local jammed structures. This allows us to follow how the system samples the landscape as a function of occupied volume fraction ϕ. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 79 publications
(100 reference statements)
0
27
0
Order By: Relevance
“…Numerical simulations can be performed in any physical dimensions, and the range d = 1 − 12 was explored in that context. [146][147][148][149] Even the space topology can be varied. 150,151 One can study the effect of freezing a subset of particles with arbitrary geometries by means of computer simulations.…”
Section: Computer Simulations Of Glass-forming Liquidsmentioning
confidence: 99%
“…Numerical simulations can be performed in any physical dimensions, and the range d = 1 − 12 was explored in that context. [146][147][148][149] Even the space topology can be varied. 150,151 One can study the effect of freezing a subset of particles with arbitrary geometries by means of computer simulations.…”
Section: Computer Simulations Of Glass-forming Liquidsmentioning
confidence: 99%
“…They also are of keen theoretical interest because they lend themselves to exact analytical treatments [6], and thus to insight into the nature of phase transitions in higher-dimensional systems. One way to partly bridge the gap between 1D and higher dimensions is to consider quasi-one-dimensional (q1D) models, which can be construed as strongly confined versions of higherdimensional systems (with a single unbounded dimension) [7][8][9][10][11][12]. These models further have experimental analogues in the trapping of fullerenes within nanotubes [13,14], the self-assembly of nanoparticles within cylindrical pores [15][16][17] and the formation of colloidal wires [18].…”
Section: Introductionmentioning
confidence: 99%
“…Its dependence on packing fraction is consistent with the general picture of a crossover from fragile glass behavior at low packing fractions to strong glass behavior at high packing fraction, which has been investigated previously in Refs. [2,4].…”
Section: Fig 1: (Color Online)mentioning
confidence: 99%
“…It has been frequently observed that disks moving in a narrow channel can provide useful insights into glassy behavior [1][2][3][4][5][6][7]. In a recent paper [6] two of us studied the static and dynamic properties of N disks of diameter σ, which move in a narrow channel consisting of two impenetrable walls (lines) spaced by a distance H d , such that 1 < H d /σ < 1 + √ 3/2 (see Fig.…”
Section: Introductionmentioning
confidence: 99%